Snap-, CLIP- and Halo-Tag Labelling of Budding Yeast Cells - Stagge, Franziska; Mitronova, Gyuzel Y.; Belov, Vladimir N.; Wurm, Christian A.; Jakobs, Stefan (PLOS ONE, 2013)
Fluorescence microscopy of the localization and the spatial and temporal dynamics of specifically labelled proteins is an indispensable tool in cell biology. Besides fluorescent proteins as tags, tag-mediated labelling utilizing self-labelling proteins as the SNAP-, CLIP-, or the Halo-tag are widely used, flexible labelling systems relying on exogenously supplied fluorophores. Unfortunately, labelling of live budding yeast cells proved to be challenging with these approaches because of the limited accessibility of the cell interior to the dyes. In this study we developed a fast and reliable electroporation-based labelling protocol for living budding yeast cells expressing SNAP-, CLIP-, or Halo-tagged fusion proteins. For the Halo-tag, we demonstrate that it is crucial to use the 6′-carboxy isomers and not the 5′-carboxy isomers of important dyes to ensure cell viability. We report on a simple rule for the analysis of 1H NMR spectra to discriminate between 6′- and 5′-carboxy isomers of fluorescein and rhodamine derivatives. We demonstrate the usability of the labelling protocol by imaging yeast cells with STED super-resolution microscopy and dual colour live cell microscopy. The large number of available fluorophores for these self-labelling proteins and the simplicity of the protocol described here expands the available toolbox for the model organism Saccharomyces cerevisiae.